Collaborative Governance Program GenRe Sebagai Upaya Peningkatan Kesadaran Remaja Terhadap Kesehatan Reproduksi di Provinsi DIY - Mutmainah, Nur Fitri; Katon Mahendra, Gerry (Jurnal Ilmiah Administrasi Publik, 2019)
Problems of adolescence such as unwanted pregnancy, early marriage, risky adolescent childbirth have sought attention to urgently resolve. Based on the data from family planning institute (PKBI), as many as 976 of 1.078 childbirth cases happened at age 10-18 years in 2015. This study focuses on finding out the possible collaborative dynamics in GenRe program, which aims at checking adolescence reproduction health. This research uses descriptive method with qualitative approach and case study design. Based on the research, it showed that the highly and interest power have Gubernur DIY, BPPM DIY, Dinas Dikpora DIY, Dinas Sosial DIY, Dinas Kesehatan DIY, Perwakilan BKKBN DIY between stakeholders including with power and interests low have Biro Kesra Setda DIY. Collaboration has been done through principled engagement, share motivation and capasity of join action show FP2KRR forum, but the leadership and management resources are still under expectation.